2011
DOI: 10.1007/s00276-011-0828-4
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic study of fabella and its surrounding structures in a Chinese population

Abstract: Fabellae were mainly present in the lateral head of the gastrocnemius muscle in a large proportion of the Chinese population. More than half of the cartilage fabellae were not visualized on radiograph. Its clinical significance could not be ignored by physicians and anatomists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 19 publications
2
83
1
1
Order By: Relevance
“…ment, and the described frequency of FF ranging between 20-87%. [9,10,17,18] We detected the FF with an actual ligament appearance in 11 sides in our series. Any fibrous structure coming from the FH and attached to the capsule, without reaching to femoral epicondyle, was discriminated from the FF and indicated as AL.…”
Section: Tablementioning
confidence: 78%
See 2 more Smart Citations
“…ment, and the described frequency of FF ranging between 20-87%. [9,10,17,18] We detected the FF with an actual ligament appearance in 11 sides in our series. Any fibrous structure coming from the FH and attached to the capsule, without reaching to femoral epicondyle, was discriminated from the FF and indicated as AL.…”
Section: Tablementioning
confidence: 78%
“…Some authors have suggested that FF is seen only in the presence of the fabella, [12,29] while some others stated that it can be found even in the absence of fabella. [17,32] Zeng et al [9] proposed that the presence of fabella did not correlate with the size or frequency of FF, whereas Seebacher et al [12] noted that when the fabella was large, AL was absent and FF was strong. In addition, Seebacher suggested that if the fabella or its cartilaginous remnant was absent, then FF was absent and only AL was found.…”
Section: Ff and Presence Of Fabellamentioning
confidence: 99%
See 1 more Smart Citation
“…The radiographic evidence of both medial and lateral fabellae in all animals is different from humans and domestic cats. In domestic cats, the medial fabella may not be visualised radiographically (Arnbjerg and Heje, 1993) whereas in humans, both the lateral and medial fabellae may not be visualised radiographically (Zeng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and bony nature of fabellae in human adults has been found to vary, with studies showing incidence rates of 66.6% (44% bony) [8]; 23.5% (72% bony) [13]; 86.9% (56% bony) [24]; and 31% (100% bony) [3]. Almost half of fabellae carry a facet for articulation to the lateral femoral condyle [3].…”
Section: Introductionmentioning
confidence: 99%